Water-Restrained Hydrogel Electrolytes with Repulsion-Driven Cationic Express Pathways for Durable Zinc-Ion Batteries - Dewu Lin; Yushuang Lin; Ruihong Pan; Jiapei Li; Anquan Zhu; Tian Zhang; Kai Liu; Dongyu Feng; Kunlun Liu; Yin Zhou; Chengkai Yang; Guo Hong; et al. (Nano-Micro Letters)
Highlights A novel cationic hydrogel electrolyte is prepared to address a significant challenge of balancing the tripartite trade-offs of hydrogel properties. Cationic express pathways enable fast and selective Zn2+ transport through dynamic ionic repulsion, achieving high ionic conductivity (28.7 mS cm−1) and Zn2+ transference number (0.79). The hydrogel demonstrates exceptional cycling stability across − 15 to 60 °C, showcasing great potential for practical flexible battery applications.